2008
DOI: 10.1242/jeb.020479
|View full text |Cite
|
Sign up to set email alerts
|

To bend a coralline: effect of joint morphology on flexibility and stress amplification in an articulated calcified seaweed

Abstract: SUMMARYPrevious studies have demonstrated that fleshy seaweeds resist wave-induced drag forces in part by being flexible. Flexibility allows fronds to ʻgo with the flowʼ, reconfiguring into streamlined shapes and reducing frond area projected into flow. This paradigm extends even to articulated coralline algae, which produce calcified fronds that are flexible only because they have distinct joints (genicula). The evolution of flexibility through genicula was a major event that allowed articulated coralline alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 29 publications
1
57
0
Order By: Relevance
“…For an ideal solid, strength and compliance are independent of strain rate. In our tests, breaking stress was independent of strain rate across a wide range of rates, and the compliance measured at a strain rate of several hundred per second is comparable to that measured by Martone (Martone and Denny, 2008b) suggests that if compliance were to decrease with increasing strain rate (as it would in a typical viscoelastic material), stress in a basal joint would increase substantially, amplifying the likelihood of failure. However, because compliance is functionally independent of strain rate, genicula have the same flexibility across a wide range of loading regimes, a potential advantage in flow as unpredictable as that of breaking waves.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…For an ideal solid, strength and compliance are independent of strain rate. In our tests, breaking stress was independent of strain rate across a wide range of rates, and the compliance measured at a strain rate of several hundred per second is comparable to that measured by Martone (Martone and Denny, 2008b) suggests that if compliance were to decrease with increasing strain rate (as it would in a typical viscoelastic material), stress in a basal joint would increase substantially, amplifying the likelihood of failure. However, because compliance is functionally independent of strain rate, genicula have the same flexibility across a wide range of loading regimes, a potential advantage in flow as unpredictable as that of breaking waves.…”
Section: Discussionsupporting
confidence: 79%
“…9) and one might suppose that this accumulated strain could threaten the joints. But Martone and Denny (2008b) have shown that an increase in genicular length increases a basal joint's flexibility, and, for strains less than 50%, the increase in flexibility is accompanied by negligible change in tensile stress. We estimate that basal genicula creep by maximally 36% over a 6 year lifetime (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some coralline algae -the erect, articulated corallines -have avoided this limitation through the evolution of joints (genicula) that allow their fronds to be as flexible as those of other seaweeds. The flexibility provided by these joints depends on the unusual mechanical properties of the genicular tissue (Martone and Denny, 2008;Janot and Martone, 2016), and these properties are best understood for Calliarthron cheilosporioides Manza, a representative articulated coralline found on the West Coast of North America.…”
Section: Introductionmentioning
confidence: 99%
“…In order for the frond (technically, the thallus) of a coralline alga to have the same flexibility as that of non-calcified algae, the genicula (which comprise only ~15% of branch length) (Martone and Denny, 2008a) must be more flexible than the tissues of fleshy seaweeds. This increased flexibility is achieved through a combination of morphology and material properties (Martone, 2006;Martone and Denny, 2008a).…”
Section: Introductionmentioning
confidence: 99%